Differences in Mathematical Performance, Creativity Potential, and Need for Cognitive Closure between Chinese and Australian Students. (28th June 2014) - Ma, Choi‐Chi Evelene; Rapee, Ronald M.
Abstract: Research has shown that Chinese students outperform students from several Western countries on mathematics performance while some evidence has suggested that Western students perform more strongly on tests of creativity. One potential mechanism for these differences may be a higher need for cognitive closure among Chinese students. The current research compared performance on tests of mathematics and creativity among 50 students of Chinese background and 49 Australian students of Anglo‐Saxon background. As predicted, Chinese students performed better on mathematics while Australian students performed better on the measure of creativity. Australian students also had a lower score on one subscale of the need for cognitive closure, preference for predictability. Across the sample, preference for predictability showed small but significant negative correlations with several measures of creativity and positive correlations with several measures of mathematics. These findings were interpreted with respect to characteristic educational practices in both nations.